2010
DOI: 10.1134/s156009041005009x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the alkyl fragment of initiating alkoxyamine in nitroxide mediated polymerization of styrene

Abstract: The role of the alkyl fragment of alkoxyamine initiating the homopolymerization of styrene is experimentally and theoretically studied in the case of 2,2,6,6 tetramethylpiperidine 1 oxyl derivatives. The rate constants of homolysis and recombination are measured for the alkoxyamines under study. The charac teristics of polymerization initiated by these compounds are experimentally examined. The kinetics of poly merization is theoretically calculated with allowance for the measured kinetic parameters and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…To validate this assumption, simulations have been performed using a difference in reactivity of one order of magnitude between the initiator radicals and the propagating radicals for the addition to styrene. In agreement with the experimental findings reported by Zubenko et al [32] and by Ananchenko et al, [30,31] the simulations revealed no influence of the first addition of the initiator radical on the kinetics of the NMP of styrene in the presence of TEMPO-1-phenylethyl or SG1-1-phenylethyl. Using kinetic modeling, also the importance of chain transfer to trimer has been assessed and was found to be insignificant in the conditions studied in this work.…”
Section: Chain Transfersupporting
confidence: 92%
See 4 more Smart Citations
“…To validate this assumption, simulations have been performed using a difference in reactivity of one order of magnitude between the initiator radicals and the propagating radicals for the addition to styrene. In agreement with the experimental findings reported by Zubenko et al [32] and by Ananchenko et al, [30,31] the simulations revealed no influence of the first addition of the initiator radical on the kinetics of the NMP of styrene in the presence of TEMPO-1-phenylethyl or SG1-1-phenylethyl. Using kinetic modeling, also the importance of chain transfer to trimer has been assessed and was found to be insignificant in the conditions studied in this work.…”
Section: Chain Transfersupporting
confidence: 92%
“…[56] As pointed out by Bagryanskaya et al, [64] the addition of the initiator radical can play an important role in the NMP of styrene if it competes with the H-transfer side reaction between the initiator radical and the nitroxide. However, experimental studies reported by Zubenko et al [32] and by Ananchenko et al [30,31] have shown that for the alkoxyamines considered in this work, i.e., TEMPO-1-phenylethyl, TEMPO-polystyrene, SG1-1-phenylethyl, SG1-polystyrene, the H-transfer reaction between the initiator radical and the nitroxide is unimportant. It can thus be expected that the addition of the initiator radical to styrene will not play a crucial role in the kinetics of the polymerization of styrene in the presence of TEMPO-1-phenylethyl or SG1-1-phenylethyl (see further).…”
Section: Chain Transfermentioning
confidence: 90%
See 3 more Smart Citations